Perancangan Jaringan Komputer Berbasis Mikrotik Router OS Pada SMAN 4 Praya - Sopian Sumardi; Mohammad Taufan Asri Zaen (LPPM STMIK Lombok, 2018)
Information and Communication Technology (ICT) is a very important requirement in the implementation of education. Becoming a necessity for SMAN 4 Praya as an upper secondary educational institution to build computer network technology considering the complexity of the problems faced in the administrative system as well as the teaching and learning process. ICTs need to be well-designed to ensure that resources can be utilized optimally and mission vision can be achieved as expected. The design of computer networks at SMAN 4 Praya uses the Network Development Life Cycle (NDLC) approaches as a development method, covering a number of stages analysis, design, prototype simulation, implementation, monitoring and management. The process of analysis is divided into several processes, namely user needs analysis, device requirement analysis (hardware, software, brainware), network needs analysis, feasibility analysis (feasibility of infrastructure and human resource feasibility), and through network topology analysis by designing architecture and computer network design. Network Design Local Area Network (LAN) and Wireless Fidelity (WiFi) based on Mikrotik RouterOS. Implementation of the use of Mikroutik RouterOS on the Internet network SMAN 4 Praya can provide effective and optimal results to divide the bandwidth of each client as as reserved, and allows administrators in managing the network to remain stable and provide maximum results.